Islamic spiritual guidance: an intervention model of depression disorders for type 2 diabetes Mellitus patients - Sulistyo, Andarmoyo; Harmy, Mohamed Yusoff; Berhanudin, Abdullah; Yuzana, Mohd Yusop (2019)
Depression is a psychiatric disorder linked to a number of chronic diseases. Individuals with diabetic type 2 mellitus (DM) are at high risk for depression. Depression in people with diabetes mellitus is associated with poor control of blood sugar, dietary disobedience, lack of motivation from the family, and worrying about the occurrence of complications of diabetes. The presence of depression in diabetics will ultimately worsen the condition of diabetes one suffers. Islamic Spiritual Guidance is a treatment or healing of psychological disorders that are carried out systematically based on the concepts of al-Quran and as-Sunnah. Islamic Spiritual Guidance has proven to be effective in decreasing depression and other psychological disorders. Spiritual therapy is very influential to build a sense of self-acceptance so that the client does not regret his fate and feel depressed any longer. On the contrary, the client will be able to express his feelings on life and have better mental health. The spiritual approach plays an important role in expressing feelings and providing comfort for the client. Client's acceptance toward their illness will encourage the individual to be closer to God and consider his illness as a trial from God. In Islamic spiritual therapy, the peace of heart and mind are the targets of therapy in dealing with various psychological diseases. Islamic spiritual therapy is flexible, preventive, creative and rehabilitative.